Height and volume functions for Pinus lawsonii, Pinus leiophylla, Pinus oocarpa and Pinus pringlei plantations in Guarei, São Paulo, Brazil. Issue 4 (2nd October 2019) - Mayrinck, Rafaella Carvalho; Roque, Vinicius Gontijo Rodrigues; Filho, Antonio Carlos Ferraz; Filho, Eduardo Michaloski; Arias-King, Fredo; Ribeiro, Andressa
Abstract : Inventories are time- and money-consuming. Hence, accurate equations to estimate difficult-to-measure variables are desirable, especially for species that are not commercially established, such as Pinus lawsonii, P. leiophylla, P. pringlei and P. oocarpa . This study aimed to fit height and volume models for these species and to present stand attribute values for a plantation located in Guarei, Brazil, belonging to the company Resinas Brasil. Models were assessed by the adjusted coefficient of determination, mean square error and residual plots. For P. lawsonii and P. pringlei, the best hypsometric models were those of Van Soest and Mishailof, respectively. For P. leiophylla at 3 m × 1.5 m and 3 m × 3 m spacing, the best models were the linear and Mishailof models, respectively. For P. oocarpa planted at 3 m × 1.5 m and 3 m × 3 m spacing, the best models were those of Mishailof and Van Soest, respectively. The best volume model was the logarithmic Spurr for all species, except for P. oocarpa, where the Spurr model was the best. The mean stem form factor for all species was 0.53. Mean annual increment ranged from 8.4 to 24.5 m 3 ha −1 ( P. lawsonii and P. oocarpa ), which can be considered satisfactory for plantations without genetic improvement and fertilisation, enforcing the species' commercial potential.